2014
DOI: 10.3846/1648715x.2013.866601
|View full text |Cite
|
Sign up to set email alerts
|

Do Responsible Real Estate Companies Outperform Their Peers?

Abstract: This paper investigates the relationship between corporate social and environmental performance and financial performance for a sample of publicly traded US real estate companies. Using the MSCI ESG (formerly KLD) database on seven Environmental, Social & Governance dimensions in the 2003-2010 period, and weighting the dimensions according to prominence in the real estate sector, we model Tobin's Q and annual total return in a panel data framework. The results indicate a positive relationship between ESG ratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 30 publications
(34 reference statements)
5
31
1
3
Order By: Relevance
“…For instance, Cajias et al . () show that, although driven by ESG concerns rather than strength, a high overall ESG rating positively affects market value. In an earlier study, Newell et al .…”
Section: Reits and Corporate Social Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Cajias et al . () show that, although driven by ESG concerns rather than strength, a high overall ESG rating positively affects market value. In an earlier study, Newell et al .…”
Section: Reits and Corporate Social Responsibilitymentioning
confidence: 99%
“…In fact, there is evidence to suggest that a high CSR rating does not have a negative impact on the financial performance of REITs. For instance, Cajias et al (2014) show that, although driven by ESG concerns rather than strength, a high overall ESG rating positively affects market value. In an earlier study, Newell et al (2011) found that CSR A-REITs did not significantly underperform non-CSR A-REITs, and also provide additional portfolio diversification benefits.…”
Section: Gpt Groupmentioning
confidence: 99%
“…(2012,) also suggested that green buildings were able to generate increased revenues. Work by Cajias et. al.…”
Section: Commercial Property In Europe and Sustainability Agendasmentioning
confidence: 99%
“…On the one hand, evidence shows that CSR can lower the cost of equity (El Ghoul et al 2011;Cajias et al 2014), lower the cost of bank loans (Goss & Roberts 2011), create rent premiums (Eichholtz et al 2010), reduce stock price crash risk (Kim et al 2014), and increase operating performance (Eichholtz et al 2012). However, many studies have found no relationship between CSR and financial performance (see Margolis et al [2009] for a review).…”
Section: Csrmentioning
confidence: 99%
“…The commonly used method form the aggregate CSR score for each firm-year by subtracting the number of concerns from the number of strengths (El Ghoul et al 2011;Kim et al 2014;Jha & Cox 2015). However, as noted by Cajias et al (2014), such an approach is not appropriate for real estate firms because some of the general ESG criteria are highly irrelevant to real estate firms. They revise the average aggregation method to a weighted average approach.…”
Section: Measurement Of Csr Performancementioning
confidence: 99%